The Method of Imaginative Suggestion Assisted by the Short Film “Bapak” in Teaching Short Story Writing - Rukaya; Emah Khuzaemah; Rianto (Aksis : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2025)
This study aims to determine the effectiveness of the Imagination Suggestion method assisted by the short film media "Bapak" on class IX students of MTs NU Assalafie. This study is a quantitative study with the Quasi Experiment method. The research design applied is the Control Group Pretest Posttest Design. The data source for this study is class IX students of MTs NU Assalafie. The data collection techniques used are tests (pretest and posttest) and observation guidelines. This data analysis technique uses the Statistical Package for the Social Sciences (SPSS) version 22. The results of the study showed a comparison of the average pretest-posttest values of the experimental class with the average pretest-posttest values of the control class. The average pretest result of the experimental class was 55.85, while the average pretest value of the control class was 59.5. In its application, the Imaginary Suggestion method assisted by the short film media "Bapak" in learning to write short stories in the experimental class, while in the control class no treatment was given. So that the average posttest value of the experimental class was 81.45, while the average posttest value of the control class was 79.17. Based on the results obtained from the scores of students who received treatment were higher than the scores of students who did not receive treatment. It can be concluded that the application of the Imaginary Suggestion method assisted by the short film media "Bapak" is effective in the ability to write short stories for class IX students of MTs NU Assalafie.